National Agenda for Prevention of Healthcare‐Associated Infections in Dialysis Centers. Issue 4 (20th May 2013) - Gupta, Neil; Cannon, Marjory; Srinivasan, Arjun; ,
Abstract: Healthcare‐associated infections (HAIs) are among the leading causes of morbidity and mortality in dialysis patients. To coordinate HAI prevention efforts, the U.S. Department of Health and Human Services established the National Action Plan to Prevent Healthcare Associated Infections in End‐Stage Renal Disease Facilities. This comprehensive plan prioritizes HAI prevention practices and 5‐year evaluation targets based on the burden of disease, level of scientific evidence, and anticipated impact from the recommended intervention. As such, the Plan focuses primarily on interventions to reduce vascular access‐related complications and infections with hepatitis B and hepatitis C virus. Over the last decade, there have been several efforts to expand HAI surveillance and prevention efforts, including coordination of HAI reporting metrics across multiple national agencies, changes in financial incentives by the Centers for Medicare & Medicaid Services (CMS), and federal funding for expansion of state‐based HAI prevention programs. As a result, a paradigm shift in HAI prevention has developed. Public health officials have assumed greater responsibility in reducing the burden of HAIs and healthcare providers have become more involved in HAI prevention. Since the Plan was initially drafted, several collaborative efforts in dialysis facilities have reported a reduction in HAIs through implementation of these interventions. These early successes highlight the potential impact of coordinated action to combat HAIs in dialysis settings and this National Action Plan provides evidence‐based strategies on how best to achieve this.